CARRYING CAPACITY OF TOURISM DEVELOPMENT IN CAMERON HIGHLANDS, MALAYSIA - Mohamad, Diana; Marzuki, Azizan (PLANNING MALAYSIA, 2018)
In the beginning, tourism existed as travelling for gathering and festival by noblemen and salvation by pilgrims. Of late, tourism generally liaises with education, business and entertainment. Given that tourism is impressive in size and pervasive in society, it is utilized as a mechanism for economic development especially by the developing countries. This paper updates the current tourism situation in Cameron Highlands (CH) and it is within this paper interest to bring forward the consideration to prolong CH as one of Malaysia’s top tourism destinations.